Niepełnosprawność w Chinach. Wprowadzenie do problemu - Grzesiak, Hanna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
China is the largest developing nation in the contemporary world with more than sixty million people suffering from disability. Social attitudes towards people with disabilities have changed significantly for the last few decades as a result of the active advocacy of the disability community in China as well as governmental support for disability initiatives. The aim of this article is to present the social situation of disabled people in China. Some aspects concerning Chinese beliefs about disability will be discussed. Special attention will be paid to institutions and associations working with disabled people.